Simbolisme Haji dan Emas dalam Falsafah Haji Bugis : Perspektif Hukum Islam - Anjas Saputra; Muhammad Mulyadi; Ferdiansa Putra; Kurniati Kurniati (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2025)
In Bugis society, the Hajj pilgrimage holds deep meaning, symbolizing both spiritual and social status. The symbols of ‘Aji’ and gold are often used to affirm a person's elevated position after completing the Hajj, indicating a rise in their social standing. This study is crucial to understanding how the Hajj influences the social and spiritual structure of Bugis society. This article aims to explore the symbolic meaning of ‘Aji’ and gold in the context of post-Hajj social-spiritual status within the Bugis community. The research utilizes library research methods with Islamic law and social anthropology approaches to analyze the relationship between the Hajj and social status. The findings indicate that the title ‘Aji’ not only symbolizes piety but also enhances the individual’s social status within the community. Gold as a status symbol further reinforces this social influence, creating a new hierarchy based on spiritual and economic achievements. Academically, it is recommended to view this phenomenon as an integration between religious values and local culture, and to deepen cross-disciplinary studies on the role of Hajj in the social structures of Muslim communities.